Development of a PM 2.5 sampler with inertial impaction for sampling airborne particulate matter - Intra P. (2014)
A simple and low cost PM 2. 5 impactor for sampling airborne particulate matter was developed, designed and evaluated. The design was an assembly of an acceleration nozzle and an impaction plate. Particles with sufficient inertia were unable to follow air streamlines and impacted on the plate. Smaller particles followed the streamlines, avoided being captured by the plate and could then be collected on a downstream filter. Analytical and numerical models were formulated to predict collection efficiency, flow fields and vectors, and particle trajectories in the impactor. The modeling suggested that an optimal operational domain exists for the PM 2. 5 impactor. A prototype was then built and tested. The collected particles on the impaction plate and downstream of the PM 2. 5 impactor were analyzed by using scanning electron microscopy. Experimental results agreed well with the theoretical predictions. Testing of the PM 2. 5 impactor prototype showed promising results for this airborne particulate matter sampler. © 2012 Korean Institute of Chemical Engineers, Seoul, Korea.